Pharo by Example 5.0 - Ducasse, Stéphane; Zagidulin, Dmitri; Hess, Nicolai; Chloupis, Dimitris (Open textbook library., 2016)
Pharo is an open-source, elegant and pure object-oriented language that supports truly immersive and life programming experience. Pharo offers excellent tools such as hot-debuggers and on the fly code update that change the programming experience. More at http://www.pharo.org.Pharo is a powerful language and IDE that companies use to deliver complex business-effective applications. More at: http://www.pharo.org/success In Pharo everything is an object, and anything can change at run-time under your fingers. Pharo is written in itself you can explore a complete world. You can feel and talk to objects. But Pharo does not stop there, with Pharo you can improve your object-oriented skills by rediscovering the essence of object-oriented programming. Pharo by Example 50, intended for both students and developers, will guide you gently through the Pharo language and environment by means of a series of examples and exercises. This book is available under the Creative Commons Attribution-ShareAlike 3.0 license.